Capillary introduction mass spectrometry coupled with selective cryotrapping for analysis of volatile compounds in water. Issue 41 (10th September 2019) - Xu, Siyu; Shi, Wenyan; Yu, Quan; Wang, Xiaohao
Abstract : This study aims to improve sampling efficiency by coupling capillary introduction (CI) with cryotrapping to implement selective removal of water. Abstract : Capillary introduction mass spectrometry (CI-MS) has been recently developed for the direct analysis of volatile organic compounds (VOCs) in liquid samples. It exhibits the merits of simple structure, easy operation, and minimal sample consumption. For CI-MS analysis of aqueous solutions, the injection rate is generally a few microliters per minute. As the dominant component of the solution, water is drawn into the instrument together with the dissolved solutes, and it may reduce the ionization efficiency of the analytes and cause spectral interference. This proof of concept study aims to improve sampling efficiency by coupling CI with cryotrapping to implement selective removal of water. With the use of a cryotrap cooled by drikold, water vapor is effectively condensed to cause more than 90% reduction of its ion signal, whereas the detection of other components is less affected. Therein, the ion signals of the dissolved air are only slightly reduced, and the ethanol and toluene signals decrease by less than 50%. The chamber pressure drops substantially during the cryotrapping CI process, enabling a high injection rate of liquid samples to improve the detection efficiency of the uncondensed analytes. In addition, to prevent the solution from freezing at the capillary outlet in vacuum, an appropriate high voltage is applied onto the sample to initiate an electrospray (ES) at the capillary tip and increase the injection rate. On the basis of this cryotrapping ES-CI strategy, the MS detection sensitivity for ethanol in water can be improved by 29.5 times compared with conventional CI-MS, and the detection limit of the established instrument can be greatly reduced. In conclusion, selective cryotrapping is a simple and practical method to promote CI-MS analysis of VOCs in water.